A Impact of shooting variation training and keteptan training on the kick ball against the shooting skills of Satria Kencana academic soccer player in 2019 (Universitas Negeri Semarang, 2020)
The background to the problem is the lack of technical skills and accuracy of shooting academy players. The formulation of the problem in this study is how much influence the variation of shooting exercises and the accuracy of kicking the ball on the ability of shooting academy players. the purpose of this study was to find out how much influence the variety of shooting exercises and the accuracy of kicking at Satria Kencana Serasi Academy Football Players in 2019. This type of research was experimental. The results showed that the calculation of paired samples test showed a significance value of 0.000 (<0.05). Shows that there is a significant effect between shooting variation training and the accuracy of kicking the ball on shooting ability. The results of R Squre calculation, the coefficient of determination obtained by 0.241 shows that the contribution of shooting variation and kicking ability to shooting ability is 24.1%. The conclusion of this study is that there is a positive and significant relationship between shooting variation practice and the accuracy of kicking the ball together to the shooting ability of SKS Academy players. There was a contribution of 24.1% of the shooting variation and accuracy of kicking the ball towards the shooting ability of the Akadami SKS player. The suggestion from this study is that a coach must have variations to practice and provide training methods that are appropriate to the characteristics of the players in order to improve their abilities both as a team and individually.